Construction and practice of a stratified training program based on nursing clinical ladder model and Benner novice to expert theory in novice dental nurses (基于Benner理论构建口腔新手护士能级进阶分层培训体系的实施与成效) - TANG Youjia (汤有佳); DONG Xue (董雪); LI Rui (李蕊); ZHANG Xiaowei (张晓巍); DING Shanshan (丁珊珊); ZHAO Jing (赵静); WU Xuan (吴宣) (中西医结合护理)
Objective To investigate the effect of the stratified training program based on nursing clinical ladder model and Benner novice to expert Theory for novice dental nurses. Methods Based on the Benner novice to expert theory, a stratified training program using nursing clinical ladder model(N0～N4) was constructed, and the N0 level was refined into 3 levels (N01～N03). The action research method was adopted in design of differentiated training module: Emphasizing standardized training of basic skills in N01 level nurses; Strengthening the specialized ability of four-handed dentistry in N01～N02 level nurses; Enhancing nurse’s ability of patient management. An assessment system using multiple evaluation methods such as OSCE assessment, skills assessment and peer review was established. A ten-year longitudinal research on 45 novice dental nurses was conducted. Results In terms of comprehensive evaluation score, a 5. 13% increase between N01 and N02 nurses, 5. 11% increase between N02 and N03 nurses and 10. 50% increase between N01 and N03 nurses were reported. Comparison of assessment results of 10 nurses between the 1st and 3rd year of stratified training program showed that the average growth rate of the theoretical assessment, practical assessment and mini-lecture assessment was 18. 29%, 8. 69%, and 12. 19%, respectively. Conclusion The Benner theory-based stratified training system realizes the systematization and precision of nursing personnel training, and its stepwise competency development path effectively solves the problem of disconnecting the training content from clinical needs. The study confirms that it can promote professional growth by stimulating nurses' endogenous motivation, improve clinical efficiency and patient experience at the same time, and provide a theoretical basis and practical example for the construction of a long-term training mechanism for novice dental nurses (目的 探讨能级进阶模式下分层培训体系对口腔科培训护士的影响。方法 依据Benner理论“从新手到专家”的能力发展框架, 建立包含N0～N4五个能级(细分为8个亚层)的护士分层体系, 将N0层级细化分为N01～N03。采用行动研究法设计差异化培训模块: N01级侧重基础技能规范化培训, N01～N02级强化四手配合专项能力, N03级培养患者管理能力。通过OSCE考核、技能考核、同行评议等多元评价方式构建考核体系。选取2013年—2023年医院45名口腔科培训护士进行纵向实践研究。结果 分析45名培训护士的10年实践效果: N02级护士综合评分较N01级护士增长5. 13%, N03级护士综合评分较N02级护士增长5. 11%, N03级护士综合评分较N01级护士增长10. 50%。选取10名护士, 对其分层培训计划实施第1年与第3年考核成绩进行分析, 理论考核成绩增长率平均为16. 58%, 实操考核增长率平均为7. 56%, 小讲课考核增长率平均为12. 07%。结论 基于Benner理论的能级进阶培训体系实现了护理人才培养的系统化与精准化, 其阶梯式能力发展路径有效解决了培训内容与临床需求脱节问题。研究证实可通过激发护士内生动力促进专业成长, 在提升临床效率的同时改善患者体验, 为构建口腔新手护士长效培养机制提供了理论依据与实践范例。)